Radio Protective Role of Growth Hormone on Secondary Ossification Center of Growing Long Bone in Young Albino Rats - Abdul Latif Panwhar, Hemant Kumar, Muhammad Rahib Jamali, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2014)
Objective:To evaluate possible effects of Growth hormone in preventing the harmful effects of radiation on secondary ossification centers of growing long bones of young albino rats. Study Design: Experimental study. Place & Duration: Experimental work was completed in Six months duration in the department of Anatomy, Basic Medical Sciences Institute (BMSI), Jinnah Postgraduate Medical Centre (JPMC) Karachi. Material & Methods: 30 litters of 10 days age of Albino rats were taken for this study. They were divided into three groups: Group A (Control), Group B was given 5Gy gamma radiation and group C was given radiation and injection somatotrophin(Growth hormone). Each group was further subdivided into two subgroups according to their respective time period of treatment i-e., 2 and 4 weeks respectively. At the end of their respective period of study animals were anasthetised by ether. Dissection was done and their long bones i,e., humerus and femur were taken out and transferred, fixed, processed and embedded in paraffin . 5um thick longitudinal sections were cut with rotatory microtome. The tissues were stained with Alcian blue- Haematoxylin and Eosin stain for measurement of secondary ossification centers. Results: A highly significant decrease in mean secondary ossification centers was noted in irradiated subgroups as compared with control. And highly significant increase of thickness in secondary ossification centers was noted in growth hormone treated subgroups as compared to irradiated subgroups. Conclusion: Irradiation causes destruction and reduction in secondary ossification centers. Growth hormone reverses the damage.